PENERTIBAN ANGKUTAN ANTAR JEMPUT DI PROVINSI RIAU (STUDI KASUS KOTA PEKANBARU) - Rezy Pramata; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Transshipment is a public transport passenger operating in the province of Riau especially Pekanbaru city which has permission from the government of Riau Province within the scope of land transportation passengers. In the framework of the development of Riau Province, especially Pekanbaru City which is a diverse center activities, which require the support of urban infrastructure that can be utilized by the community in supporting its daily activities, both aimed within the city and that aims out of town. The control of shuttle transportation is regulated in law number 22 of 2009 on traffic and road transport.The purpose of this research is to know how the supervision done by the provincial transportation service riau in controlling the shuttle transportation in the city of Pekanbaru and to know the factors that influence the control of the shuttle transport in the city of Pekanbaru. The theoretical concept used is the Brantas theory which sees the nature and timing of supervision. This research uses qualitative research method for descriptive study. In data collection, the authors use interview techniques, observation and documentation. With the use of key informants as information sources and triangulation techniques as a source of data validity.The results of this study indicate that the supervision and control done by the provincial transportation agency riau has not been maximized, it is evident that there are still many pickup transports that violate the rules with the policies that have been set. Factors influencing the controlling of shuttle transportation are lack of human resources or inadequate personnel in conducting supervision in controlling the shuttle transportation as well as the attitude of officers who are not kosisten in cracking down transport shuttle, still lack of budget, and not yet right target and lack of knowledge And awareness of the community in choosing good and safe transportation. And the number of transport businessmen who do not understand in implementing policies.Keywords: policy, supervision, controlling